The Islamic Phenomenon in Modern Arab Countries - Muhammadong Muhammadong (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The modern Arab nation, usually referred to as a global society, is certainly different from the Arab nation during the time of the Prophet Muhammad. The difference lies in following the geo-culture that it experiences to continue its existence in the arena of international competition. Modern Arabs have been compressed in ethnolinguistics that are far from being generally Muslim so that the facts that occur are still common among those who are not Muslims. In their religious understanding, the Modern Arab nation seems monolithic and is not dominated by certain doctrines to develop its teachings. So, it is commonplace to find among them various variants, both cultural, political and governmental, to strengthen their existence.